Analisis Kelayakan Kemitraan Ayam Pedaging (Broiler) di Kota Parepare - Nurdin Nurdin; Usman Usman; Andi Syahridah (Universitas Muhammadiyah Purworejo, 2021)
Livestock development is an integral part of national development which aims to provide animal food, increase livestock income and expand employment. This study aims to determine the feasibility of breeders who partner with companies and analyze the scale of business that benefits the agribusiness of broiler chickens in a business partnership pattern. This study uses a case study research conducted in the City of Parepare from October 2019 to January 2020. The sample in this study was 22 Farmers spread across 4 (four) Districts of Parepare City by using research instruments in the form of questionnaires and related document searches. The data obtained were analyzed using income analysis and R / C Ratio. The results showed that the highest R / C Ratio at 4500-5000 business scale is 1.40, while for business scale 2500-3000 R / C Ratio is 1.16 business scale 3500-4000 R / C Ratio 1.10 business scale 5500-6000 R / C Ratio is 1.10 and business scale is 6500-7000 R / C Ratio is 1.07. The conclusion of this study is that raising livestock with a business partnership scheme is feasible to be implemented in the City of Parepare and the highest profit from livestock business is carried out with a partnership pattern on a business scale of 4500-5000 tails in the period November - December 2019.